<u>Given </u>that the functions
and ![g(x)=x^{3}](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E%7B3%7D)
We need to determine the value of the function ![(g \ {\circ} f)(-3)](https://tex.z-dn.net/?f=%28g%20%5C%20%7B%5Ccirc%7D%20f%29%28-3%29)
First, we shall determine the composition of the function ![(g \circ f)(x)](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29)
<u>Function </u>
<u>:</u>
Let us determine the function ![(g \circ f)(x)](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29)
Thus, we have;
![(g \circ f)(x)=g[f(x)]](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29%3Dg%5Bf%28x%29%5D)
![=g[x+4]](https://tex.z-dn.net/?f=%3Dg%5Bx%2B4%5D)
![=(x+4)^3](https://tex.z-dn.net/?f=%3D%28x%2B4%29%5E3)
![(g \circ f)(x)=x^3+3x^2(4)+3x(4)^2+(4)^3](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29%3Dx%5E3%2B3x%5E2%284%29%2B3x%284%29%5E2%2B%284%29%5E3)
![(g \circ f)(x)=x^3+12x^2+48x+64](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29%3Dx%5E3%2B12x%5E2%2B48x%2B64)
Thus, the function is ![(g \circ f)(x)=x^3+12x^2+48x+64](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29%3Dx%5E3%2B12x%5E2%2B48x%2B64)
<u>Value of the function </u>
<u>:</u>
The value of the function can be determined by substituting x = -3 in the function ![(g \circ f)(x)=x^3+12x^2+48x+64](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29%3Dx%5E3%2B12x%5E2%2B48x%2B64)
Thus, we have;
![(g \circ f)(-3)=(-3)^3+12(-3)^2+48(-3)+64](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28-3%29%3D%28-3%29%5E3%2B12%28-3%29%5E2%2B48%28-3%29%2B64)
Simplifying the terms, we get;
![(g \circ f)(-3)=-27+12(9)+48(-3)+64](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28-3%29%3D-27%2B12%289%29%2B48%28-3%29%2B64)
![(g \circ f)(-3)=-27+108-144+64](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28-3%29%3D-27%2B108-144%2B64)
![(g \circ f)(-3)=1](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28-3%29%3D1)
Thus, the value of the function
is 1.